Pengaruh Kompensasi, Gaya Kepemimpinan, dan Motivasi Kerja Terhadap Kinerja Karyawan Generasi Z di Indonesia - Steven Keane; Alan Setiawan; Michael Abed Nego Harianja; Amal Vieri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to explain whether there is an influence of compensation (X1), leadership style (X2), and work motivation (X3) on employee performance (Y) in generation z in Indonesia. The population used in this study were young children of generation z who had entered the workforce. The sample was determined by the purposive sampling method with a total of 100 respondents. Data were collected through a questionnaire in the form of a google form that was distributed. The results of this study indicate that compensation has a negative and significant effect on the performance of generation z employees in Indonesia with a regression coefficient of t count -2.491 <t table 1.660 and a significant level of 0.017 <0.05, leadership style has a positive and significant effect on the performance of generation z employees in Indonesia with a regression coefficient of t count 13.811 <t table 1.660 and a significant level of 0.000 <0.05, work motivation has a positive and significant effect on the performance of generation z employees in Indonesia with a regression coefficient of t count 5.688 <t table 1.660 and a significant level of 0.000 <0.05, this shows that compensation has a negative and significant effect on the performance of generation z employees in Indonesia, leadership style and work motivation have a positive and significant effect on the performance of generation z employees in Indonesia.